ABRAHAM ACCORDS: PERJANJIAN NORMALISASI ANTARA NEGARA-NEGARA ARAB DAN ISRAEL - Laila Rizky Amaliya; Muhammad Hamdan Basyar; Mulawarman Hannase (Departemen Hubungan Internasional, Fakultas Ilmu Sosial dan Ilmu Politik, Universitas Padjadjaran, 2025)
The Abraham Accords are the most important agreement in the Middle East between Israel and Arab countries, such as Bahrain, the United Arab Emirates, Morocco, and Sudan. The Abraham Accord has opened the gates of bilateral relations between Arab countries and Israel and has also changed the geopolitical dynamics in the Middle East. Until now, many previous studies have viewed the Abraham Accord as a strategic collaboration aimed at enhancing influence and countering the opposing power in the Middle East. As a result, this study presents a new perspective to examine another side of the Abraham Accord, namely its economic cooperation. This research uses a qualitative method to analyze comprehensively about the economic cooperation. The Abraham Accord is a potential platform to meet economic interests between countries. Economic interests are the main drivers in the ratification of the treaty. Strategic economic interests between countries are based on the same economic orientation that has the potential to open the door to other forms of intensive economic cooperation. Economic cooperation between Arab countries and Israel is focused on the economic diversification agenda that has an impact on economic growth and development between these countries. Theoretically, this research has implications for the existence of new approaches and perspectives in studying the Abraham Accord. As for practically, this research can be a reference in formulating policies related to the Middle East.